2005
DOI: 10.1111/j.1442-9071.2005.01067.x
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand experience of I125 brachytherapy for choroidal melanoma

Abstract: Patient outcomes following brachytherapy were excellent with a high percentage of patients retaining mobility vision. Development of complications was related to the tumour location and dose to non-tumour structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 7 publications
1
26
0
6
Order By: Relevance
“…However, the ensuing radiation retinopathy results in frequent complications that compromise posttreatment vision. Radiation retinopathy has been reported to occur in 10-63% of postplaque eyes, with higher rates associated with larger tumors or increased radiation dosages or both [4][5][6][7][8][9][10][11]. In a recent Collaborative Ocular Melanoma Study of postplaque eyes that were enucleated for treatment failure, 55% of eyes demonstrated evidence of vascular abnormalities related to radiation retinopathy [12].…”
Section: Introductionmentioning
confidence: 96%
“…However, the ensuing radiation retinopathy results in frequent complications that compromise posttreatment vision. Radiation retinopathy has been reported to occur in 10-63% of postplaque eyes, with higher rates associated with larger tumors or increased radiation dosages or both [4][5][6][7][8][9][10][11]. In a recent Collaborative Ocular Melanoma Study of postplaque eyes that were enucleated for treatment failure, 55% of eyes demonstrated evidence of vascular abnormalities related to radiation retinopathy [12].…”
Section: Introductionmentioning
confidence: 96%
“…However, in the studies with I-125 brachytherapy, few reports mention scleral atrophy or necrosis as a complication. Stack et al 14 documented that none of their 84 patients developed scleral necrosis after I-125 brachytherapy.…”
Section: Scleral Necrosismentioning
confidence: 99%
“…Higher radiation dose and tumours with thickness greater than 4 mm increase the risk for radiation maculopathy. 14 Stack et al 14 found a 63% risk for radiation maculopathy if the dose to the macula exceeded 90 Gy. A decreased distance to the foveola as well as male gender have also been associated with a decreased time to maculopathy.…”
Section: Pathogenesis and Clinical Features Of Radiation-induced Retimentioning
confidence: 99%
“…The major modifiable risk factor for development of radiation maculopathy is the total dose of radiation to the macula [18]. Newer designs/techniques of delivering radiation should be explored [6,7,8,13,19,20]. The other option of attenuating intraocular radiation by temporarily filling the vitreous cavity with silicone oil is also under investigation [21].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…The risk of radiation maculopathy is increased in the presence of comorbidities such as diabetes and prior chemotherapy [6,7,8]. In addition, several modifiable radiation factors such as the type of radiation delivery method (teletherapy vs. brachytherapy), fractionation, type of radiation isotope used for brachytherapy (ruthenium-106 vs. iodine-125) and the total dose delivered to the macula also significantly influence the risk of developing radiation maculopathy [9].…”
Section: Risk Factorsmentioning
confidence: 99%